Clinical, demographic characteristics and results of the long term follow-up in adolescents and adults with congenital heart disease - I.G. Lebid (Кардіохірургія та інтервенційна кардіологія)
The aim – to analyze clinical and demographic indicators in adolescents and adults with congenital heart disease (CHD) to provide strategy of cardiac care for these patients, to assess risk of cardiological and cardiac surgery interventions in patients with congenital heart malformations. Materials and methods. 2569 consecutive patients, aged 16–88 years, mean age 24.14 ± 0.20 years, were selected in electronic database from April 01, 2011 to December 31, 2015. The majority (92.57 %) of the included patients (n = 2378) were younger than 40 years. Results. Among all CHD patients, a significant majority had septal defects (39 %) and left heart lesions (24 %), followed by congenital lesions of thoracic arteries and veins (16 %) and right heart lesions (10 %). The annual number of the examined patients with CHD progressively increased (from 210 in 2011 to 656 in 2015). The number of patients aged 18 years or older mostly increased. The number of patients older than 40 years increased from nine patients in 2011 to 75 adults in 2015. Patients after cardiac surgery and percutaneous transcatheter interventions dominated (n=1553, 60.45 %), compared to the patients without any interventions for CHD (n = 1016, 39.55 %). Only one intervention for CHD was performed in the majority of these patients (n = 1255, 80.81 %), 12.94 % needed two interventions, 3.99 % – three, 2.26 % – three or more interventions. Conclusions. Among patients with congenital heart disease, patients younger than 40 years old were prevalent (92.57 %), with no significant gender differences. Septal defects (ASD, VSD), left heart lesions (congenital aortic valve stenosis and insufficiency), congenital lesions of thoracic arteries and veins (patent ductus arteriosus and aorta coarctation) were registered most often in adolescents and adults.